Action-based cognitive remediation in bipolar disorder improved verbal memory but had no effect on the neural response during episodic memory encoding. (January 2022) - Macoveanu, Julian; Damgaard, Viktoria; Ott, Caroline V.; Knudsen, Gitte M.; Kessing, Lars V; Miskowiak, Kamilla W
Highlights: Patients with bipolar disorder show cognitive impairments. Patients showed picture encoding-related hypoactivity in dorsal prefrontal cortex. Action-Based cognitive remediation improves executive function and verbal memory. ABCR was not associated with significant task-related neuronal activity changes. Abstract: Verbal memory and executive function impairments are common in remitted patients with bipolar disorder (BD). We recently found that Action-Based Cognitive Remediation (ABCR) may improve executive function and verbal memory in BD. Here, we investigated neuronal changes associated with ABCR treatment-related memory improvement in a longitudinal functional MRI (fMRI) study. Forty-five patients with remitted BD (ABCR: n = 26, control treatment: n = 19) completed a picture-encoding task during fMRI and tests of verbal memory and executive function outside the scanner before and after two weeks of ABCR/control treatment. The cognitive assessment was performed again following ten weeks of treatment. Thirty-four healthy controls underwent the same test protocol once for baseline comparisons. Patients showed a moderate improvement in a domain composite of verbal learning and memory both after two weeks and ten weeks of ABCR treatment, which correlated with improved executive function. At baseline, patients showed encoding-related hypoactivity in dorsal prefrontal cortex compared to healthy controls. However, treatment was not associated with significant task-related neuronal activity changes. Improved verbal learning and memory may have occurred through strengthened strategic processing targeted by ABCR. However, picture-encoding paradigms may be suboptimal to capture the neural correlates of this improvement, possibly by failing to engage strategic encoding processes.